مساهمة التدقيق الداخلي ومراقبة التسيير في تطبيق الحوكمة - صحراوي, فارس; فريحي, محسن (جامعة الوادي - University of Eloued, 2020)
تهدف هذه الدراسة إلى توضيح مساهمة التدقيق الداخلي ومراقبة التسييرفي تطبيق حوكمة المؤسسات، بكونهما أحد الأسس التي ترتكز عليها حوكمة المؤسسات انطلاقا من مبدأ الفصل بين الإدارة والملكية، حيث تم التطرق إلى كل من مفهوم حوكمة المؤسسات والتدقيق الداخلي ومراقبة التسيير وعلاقة التي تربط بين التدقيق الداخلي ومراقبة التسيير وبالإضافة إلي دور كل من التدقيق الداخلي ومراقبة التسيير في تطبيق حوكمة في الإطار النظري، وذلك بالاعتماد على المنهج الوصفي. This study aims to clarify the contribution of internal audit and management control in the application of corporate governance, as one of the foundations of corporate governance based on the principle of separation of management and ownership, where the concept of institutional governance, internal audit and management control was addressed. The relationship between internal audit and management control, as well as the role of internal audit and management control in the application of governance in the theoretical frameworkisbased on the descriptive approach.
Keywords: حوكمة المؤسسات، التدقيق الداخلي، مراقبة التسيير. ; Corporate Governance, Internal Audit, Governance Control.